APLIKASI MOBILE SEBAGAI SARANA INFORMASI LOKASI RUMAH KOST DI DAERAH ISTIMEWA YOGYAKARTA MOBILE APPLICATION AS A MEANS OF BOARDING HOUSE LOCATION INFORMATION IN “DAERAH ISTIMEWA YOGYAKARTA” - Indra Kurniawan; Muhammad Sholeh; Uning Lestari (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
Boarding house is a kind of a rented rooms leased during a certain period of time according with the agreement with the owner and the agreed price. Generally rent a room done for a year. But sometimes people rented for a month, three month, and six month, so they called it a year rented, three month rented, and half year rented. Boarding house is very usefull for a student or people who studied or working outside the town. The materials used in this study is data obtained from observation metode, the study of library, and analysis. This mobile aplication as a means of boarding house location information is buid by JAVA programing language, MySQL database, Google Maps Android API, Apache web server, and Android Studio IDE. While a web aplication is buid by PHP programing language, MySQL database, Google Maps, Apache web server and Notepad++ text editor. This mobile aplication as a means of boarding house aplication is helping people as a user to get some information and boarding house information. This aplication helping a boarding house owner to advertise their boarding house with inserting data via website.